2023
DOI: 10.1111/jce.16076
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation approach and outcome in HIV+ patients with recurrent atrial fibrillation

Vincenzo Mirco La Fazia,
Nicola Pierucci,
Sanghamitra Mohanty
et al.

Abstract: IntroductionEarlier studies have shown a clear association between severity of human immunodeficiency virus (HIV) infection and incident atrial fibrillation (AF). We present the long‐term outcome of catheter ablation (CA) and electrophysiological characteristics in HIV+ AF patients.MethodsThis study evaluated 1438 consecutive AF patients [31 (2.15%) with HIV and 1407 (97.8%) without HIV diagnosis] undergoing their first CA at our center. A total of 31 HIV patients and 31 controls were generated by propensity m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…It is also important to mention that alongside SARS-CoV-2, there are also other viruses than may result into manifestation of AF and can be detrimental for atrial function and cause AF in a proportional way to the severity of HIV disease ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to mention that alongside SARS-CoV-2, there are also other viruses than may result into manifestation of AF and can be detrimental for atrial function and cause AF in a proportional way to the severity of HIV disease ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…This study provides insights into the long-term efficacy and safety of ablation index-guided AF ablation for atrial fibrillation. Although long-term data are available on select patient cohorts ( 22 ), for the first time, this study presents long-term follow-up (beyond 5 years) data in a cohort of real-world consecutive patients utilising the ablation index and a pragmatic pre-defined ablation escalation strategy. Five-year data are particularly useful when counselling patients on treatment options as a common concern for them is the prognosis beyond the typically studied 1-year window.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, catheter ablation is the first choice in ERC treatment. La Fazia et al ( 28 ) found that human immunodeficiency virus (HIV) patients with AF have more serious inflammation and oxidative stress caused by HIV infection, which can contribute to atrial remodeling and AF burden ( 28 ). For HIV + AD patients, undergoing catheter ablation earlier can significantly reduce the incidence of atrial arrhythmias.…”
Section: Discussionmentioning
confidence: 99%